GOING GENTLY INTO THAT GOOD NIGHT: THE CONSTITUTIONALITY OF CONSENT IN CASES OF EUTHANASIA - Samantha Krause (Obiter, 2021)
Although consent is a justification ground in South African law, its applicability to cases of euthanasia has been the subject of controversy. It is submitted that relying on the distinction between omission and commission, or causation or intent will not prove useful in justifying mercy killing. In terms of the South African Constitution (and various human rights guaranteed therein), there may be compelling arguments for legalizing euthanasia. For instance, section 10 of the Constitution guarantees the right to dignity. A lack of control over your destiny essentially involves a loss of dignity. Further, the right to dignity and the qualified right to personal autonomy inform section 14: the right to privacy. This right holds that an individual can make certain fundamental private choices without state interference. Surely this would extend to how to end one’s life? This article advocates that a rights-based approach be used to inform the doctrine of consent. This would entail taking the victim’s shared responsibility into account thereby reducing the perpetrator’s fault.